2022
DOI: 10.25165/j.ijabe.20221506.7351
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, growth, and physiological traits of greenhouse cucumber seedlings as affected by supplementary white and blue LEDs

Abstract: Supplemental lighting can be applied in the greenhouse to obtain high-quality seedlings when the solar daily light integral (DLI) is insufficient. However, there is no optimal strategy for the supplementary light provided by white and blue light-emitting diodes (LEDs) with the same DLI in cucumber (Cucumis sativus L.) seedling production grown in the greenhouse in early spring. The objective of the study was to determine changes in morphology, photosynthesis, growth, and physiological characteristics in greenh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…The chlorophyll content of lettuce grown under supplementary light was significantly higher compared with the control (Figure 1). Similar trends were observed under supplementary lighting in tomato [49] and cucumber seedlings [50] grown under greenhouse conditions. Light intensity and quality can regulate chlorophyll synthesis through a physiological process mediated by phytochromes [51].…”
Section: Discussionsupporting
confidence: 78%
“…The chlorophyll content of lettuce grown under supplementary light was significantly higher compared with the control (Figure 1). Similar trends were observed under supplementary lighting in tomato [49] and cucumber seedlings [50] grown under greenhouse conditions. Light intensity and quality can regulate chlorophyll synthesis through a physiological process mediated by phytochromes [51].…”
Section: Discussionsupporting
confidence: 78%
“…Considering the suitable DLI and supplementary duration [13] for growth of cucumber seedlings, they were grown under supplemental DLI at 6.5 mol m −2 d −1 with a light intensity and photoperiod at 180 µmol m −2 s −1 and 10 h d −1 , respectively, created by white LEDs (W) (Weifang Hengxin Electric Appliance Co., Ltd., Weifang, China), ultraviolet A LEDs (UV-A) (Xiamen Lumigro Technology Co., Ltd., Xiamen, China), the combinations of white and blue LEDs (WB) (Weifang Hengxin Electric Appliance Co., Ltd., Weifang, China), the combinations of white and UV-A LEDs (W-UVA), and the combinations of white, blue, and UV-A LEDs (WB-UVA), respectively. The ratio of combinations of blue and white LEDs and the spectral distribution of the LEDs were applied based on our previous study [37] and the supplemental light intensity of UV-A light was 15 µmol m −2 s −1 . Additionally, cucumber seedlings grown with natural light only was set as the control (DLI at 5.0 mol m −2 d −1 ).…”
Section: Treatment Designmentioning
confidence: 99%
“…Our previous study investigated the proper proportion created by white and blue LEDs for growth of greenhouse-grown cucumber seedlings [37]; nevertheless, hardly any studies have reported the influences of supplementary white or white plus blue LEDs combined with UV-A on the leaf morphology, pigment content, photosynthetic traits, biomass accumulation, root architecture, and hormone contents of cucumber seedlings grown in the greenhouse. The results could provide guidelines for the regulation of supplemental light strategies for greenhouse-grown cucumber seedlings produced in winter, early spring, or seasons with insufficient sunlight.…”
Section: Introductionmentioning
confidence: 99%